Quality of life of Brazilian wheelchair tennis athletes across competitive and elite levels - Vitor Ciampolini; Luis Columna; Bruno Lapolli; Tayná Iha; Erika Carter Grosso; Diego Augusto Santos Silva; Larissa Rafaela Galatti (Universidade Estadual Paulista (UNESP), 2017)
Abstract Aims This study aimed to identify Brazilian wheelchair tennis athletes' quality of life and to compare the perception scores between competitive and elite athletes. Methods Participants were wheelchair tennis athletes (N = 31) from Brazil (males = 25, females = 6) divided into two groups: competitive and elite. Data was collected using the Brazilian version of the WHOQOL-Bref. The WHOQOL-Bref asks two general questions, and is thereafter divided into four main domains: 1) physical, psychological, social, and environment, which give us an understanding of their overall quality of life perception. Results The results showed that overall, 29 out of the 31 athletes perceived their quality of life positively, regardless of the competitive level. However, statistically higher perceptions were found in the physical domain and the total score of quality of life of the elite group. Conclusion The findings of this study suggest that even though participation in high-performance adapted sports may offer a stressful and exhausting environment, elite wheelchair tennis athletes from Brazil perceive themselves as having a better QoL than competitive athletes.